Exploiting sulfinylamines in synthesis - Davies, TQ (2018)
In the following thesis, new methodologies which exploit sulfinylamine reagents to enable one-pot syntheses of a range of nitrogen-containing sulfur(VI) functional groups are documented. The union of sulfinylamines with widely available organometallic reagents and amines allows the rapid construction of complex, medicinally relevant sulfoximine, sulfonimidamide and primary sulfonamide products. Chapter 1 is a literature review covering the properties, applications and synthesis of sulfonimidamides and sulfoximines. Chapter 2 describes the development of a new strategy for the preparation of sulfonimidamides. A remarkably stable sulfinylamine reagent, N-sulfinyltritylamine (TrNSO), is identified and used in a one-pot, three component synthesis of N-H sulfonimidamides. Analogues of the anti-arthritis drug Celecoxib are prepared using the method and subjected to biological assays by collaborators at UCB Biopharma. Chapter 3 documents the discovery of a new class of sulfinylamines, O-aryl-Nsulfinylhydroxylamines, that enable the preparation of sulfoximines by the sequential addition of two Grignard reagents, or sulfonimidamides by the sequential addition of a Grignard reagent and an amine. Two possible mechanistic pathways are discussed and evaluated. Chapter 4 details the serendipitous discovery of a one-pot synthesis of primary sulfonamides from the novel reagent O-tert-butyl-N-sulfinylhydroxylamine. Preliminary mechanistic studies are presented. Chapter 5 discusses the conclusion of the research and the potential for future work. Chapter 6 presents the experimental data.